Effect of Bandotan (Ageratum conyzoides Linn) leaf extract and wild honey provision on cut wound healing in mice - Vivi Chairun Nisa; Syamsu Rijal; Marzelina Karim; Rachmat Faisal Syamsu; Dzul Ikram (International Journal of Health Science and Technology, 2025)
Cuts are a common form of injury caused by trauma from sharp objects such as knives, razor blades, or other sharp objects. In Indonesia, traditional wound treatment is still widely used, one of which is by using Bandotan leaves (Ageratum conyzoides Linn), which is known to have the ability to stop bleeding and accelerate wound healing. In addition, wild honey from Apis dorsata bees also contains various active compounds that can be significant for the wound healing process. Data from Riskesdas (Riset Kesehatan Dasar - Basic Health Research) showed that the prevalence of cut/slash/stab wound cases in South Sulawesi in 2018 reached 27.76%, so an effective and natural alternative treatment is needed. This study aims to determine the content of phytochemical compounds in Bandotan leaf extract and wild honey; and compare their effectiveness on cut healing in mice (Mus musculus), both macroscopically and histologically. This study employed a quantitative experimental method with a Pretest-Posttest Control Group Design. The results show that Bandotan leaf extract contains alkaloids, flavonoids, steroids, and saponins; while wild honey contains flavonoids and saponins. Macroscopically, wild honey is more effective in accelerating wound healing than the other groups. However, microscopically, the Bandotan leaf group shows higher epidermal thickness. Complete re-epithelialization occurs in all groups, while keratinization does not only occur in the negative control group. In conclusion, wild honey is more clinically effective in accelerating wound healing, while Bandotan leaves show potential for tissue regeneration based on histology.